Effects of Acupressure on Psychological Symptoms in Chronic Disease Patients: A Scoping Review - Hanifah Sahar Al Afra; Fitria Handayani; Meria Erawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Research related to the effects of acupressure on psychological problems in patients with chronic diseases has been conducted by previous researchers. However, so far reviews on this topic are still limited. The purpose of this review is to obtain an overview of the extent of the effects of acupressure on psychological symptoms of chronic disease sufferers based on the results of research that has been conducted. The method used is a scoping review, determining the research questions to be reviewed using the PICO (Population, Intervention, Comparison, Outcome) framework. The keywords used in the article search are